New Insights Into the Role of RNA-Binding Proteins in the Regulation of Heart Development. - Ladd, A. N.
The regulation of gene expression during development takes place both at the transcriptional and posttranscriptional levels. RNA-binding proteins (RBPs)regulate pre-mRNA processing, mRNA localization, stability, and translation. Many RBPs are expressed in the heart and have been implicated in heart development, function, or disease. This chapter will review the current knowledge about RBPs in the developing heart, focusing on those that regulate posttranscriptional gene expression. The involvement of RBPs at each stage of heart development will be considered in turn, including the establishment of specific cardiac cell types and formation of the primitive heart tube, cardiac morphogenesis, and postnatal maturation and aging. The contributions of RBPs to cardiac birth defects and heart disease will also be considered in these contexts. Finally, the interplay between RBPs and other regulatory factors in the developing heart, such as transcription factors and miRNAs, will be discussed.
Keywords: RNA-BINDING PROTEIN; POSTTRANSCRIPTIONAL REGULATION; HEART DEVELOPMENT; MORPHOGENESIS; CARDIAC BIRTH DEFECTS; CARDIOMYOPATHY